Fungi of the human gut microbiota: Roles and significance - J. Christian Pérez (Elsevier, 2021)
It is becoming increasingly clear that fungi are important components of the gut microbiota. Fungi residing in the human intestine, for example, elicit the induction of T helper 17 cells, which are central orchestrators of protective immune responses. Likewise, fungal members of the intestinal microbiota have been shown to influence the immunological responses of the mammalian host by dampening or promoting local inflammatory responses. Here I review some of the latest developments regarding symbiotic fungi of the gastrointestinal tract and the consequences that fungal dysbiosis may have on human health. A major focus of the review is on the relationship between Candida albicans, the most prominent fungus inhabiting the human gut, and the mammalian host. Advances in the field underscore the need to further investigate the fungi that inhabit the human body to understand how the mixed array of microbes that constitute our microbiota contribute to health and disease.